Neutronics investgation of subcritical systems at the Yalina facility - Kiyavitskaya, Hanna I. (Journal of the Belarusian State University. Ecology, 2020)
The present work focuses on short description of the research on neutronics of subcritical system at the subcritical facility «YALINA». This work yields a number of innovative results: (a) provides argumentation for the concept of using low-energy accelerators (cyclotrons, neutron generators) for studying physics and kinetics of subcritical systems driven by high-energy particles accelerators; (b) shows the creation of a new functioning subcritical facility consisting of two sub-critical assemblies, a neutron generator, a measurement complex, and a life-support system. The «YALINA» facility is a unique system that has no equivalent across the world. It can be used to obtain reliable experimental data, i.e. a catalogue, that is indispensable for elaborating a technical design for an innovative industrial prototype of a subcritical reactor (accelerator-driven system, aka ADS).